Comparison of clinical and biomechanical outcomes between the kinematic and mechanical alignment methods in total knee arthroplasty: Protocol for a multicenter randomized controlled trial - Yoshinori Takashima (Contemporary Clinical Trials Communications, 2021)
Introduction: The concept of anatomic restoration has garnered considerable interest in the form of kinematically aligned total knee arthroplasty (KA-TKA). KA-TKAs have been reported to reproduce natural alignment and kinematics. However, few randomized controlled trials (RCTs) have compared the biomechanical outcomes and the long-term clinical outcomes of KA-TKA with those of mechanically aligned TKA (MA-TKA). We aim to investigate the long-term clinical and biomechanical effects of KA-TKA and to determine whether KA-TKA or MA-TKA is more appropriate for primary TKA. Methods: This trial will compare clinical and biomechanical outcomes of KA-TKA to those of MA-TKA. Two hundred patients will be enrolled in the RCT and randomized into KA-TKA or MA-TKA groups. Both the groups will be evaluated 1 week before the operation, on the day of the operation, 6 months after the operation, and 1, 5, and 10 years after the operation. The primary outcome is the difference between preoperative and 1-year postoperative functional activity scores of the 2011 Knee Society Score (2011 KSS) in both groups as well as the differences between the scores of both groups. The secondary outcomes will include differences in symptom, satisfaction, and expectation scores of the 2011 KSS, intraoperative kinematics evaluation, postoperative clinical outcomes and complications, pre- and postoperative gait analyses and radiograph evaluations between both KA-TKA and MA-TKA.